2010
DOI: 10.1093/cvr/cvq079
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rac1 overexpression in mice creates a substrate for atrial arrhythmias characterized by structural remodelling

Abstract: The substrate for atrial arrhythmias in mice with Rac1 overexpression is characterized by conduction disturbances and atrial fibrosis. Electrical remodelling (i.e. a shortening of AERP) does not play a role. Statin treatment cannot prevent the structural and electrophysiological effects of pronounced Rac1 overexpression in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 25 publications
5
33
1
1
Order By: Relevance
“…This chemical was chosen as a simple and effective agent for generating cellular oxidative stress levels without concomitant tissue injury. To date, there has not been a suitable alternative for an in vivo oxidative stress model without tissue injury (1,3,6,8,12,29,32,38). As reported in previous studies (2, 4) using PQ to generate high-level ROS to mimic disease systems, we observed a significant increase in oxidative stress markers in cardiac tissue within hours of treatment.…”
Section: Discussionsupporting
confidence: 77%
“…This chemical was chosen as a simple and effective agent for generating cellular oxidative stress levels without concomitant tissue injury. To date, there has not been a suitable alternative for an in vivo oxidative stress model without tissue injury (1,3,6,8,12,29,32,38). As reported in previous studies (2, 4) using PQ to generate high-level ROS to mimic disease systems, we observed a significant increase in oxidative stress markers in cardiac tissue within hours of treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Simultaneous Calcium and Electrophysiological RecordingsRecordings were performed as described earlier (28). For assessing the EC coupling gain we followed a protocol described in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Conditional mutant mice with cardiac-specific Hdac4 deletion were generated by crossing existing Working heart experiments. Working heart experiments were performed as described previously (42). Briefly, hearts were perfused with Krebs-Henseleit solution at 37°C in a Langendorff apparatus, paced at 400 bpm, and exposed to effective preload of 10 mmHg and afterload of 80 mmHg.…”
Section: Figurementioning
confidence: 99%